2008
DOI: 10.1159/000136655
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Subject Self-Report for Acne

Abstract: Background/Objective: Acne prevalence studies often use subject self-report as data source. Our aim was to evaluate the validity of acne self-report. Methods: Responses of university students to an acne questionnaire were compared to the trained observer’s concurrent examination of acne. The validity of self-report was measured by sensitivity, specificity, positive predictive value and negative predictive value. Agreement was measured by Cohen’s kappa and correct classification percentage. Results: The sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
5
25
1
1
Order By: Relevance
“…The few studies that looked at this problem concluded that there is lack of agreement between self-report and the trained observer acne evaluation, which is similar to our study [14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The few studies that looked at this problem concluded that there is lack of agreement between self-report and the trained observer acne evaluation, which is similar to our study [14].…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that 35.8% of students got an acne treatment without a prescription; which are most probably over the counter drugs. This is comparable to the general estimation that 30% of affected acne patients are likely to use OTC treatments [14]. Surprisingly the treatment duration expectation was less than one week in 9.9% of students and more than 2 months in 39.1% of students only.…”
Section: Discussionsupporting
confidence: 72%
“…Por outro lado, a entrevistadora não percebeu dificuldade na realização dos inquéritos. 8,10,11,23 Houve diferença significativa na idade de início da acne entre os grupos. Mesmo assim, 80% das mulheres do grupo adulto relataram o início das lesões ainda na adolescência, ratificando observações prévias de que a maioria dos casos de acne de mulheres adultas pode corresponder a persistência do quadro juvenil.…”
Section: Discussionunclassified
“…A recent study measuring the validity of self-report for acne showed that college students cannot accurately report that they have acne. 35 Again, although statistically significant, the prevalence ratios demonstrating an association between milk and acne were very low (maximum of 1.24). Thus, the clinical relevance of these results remains in question.…”
Section: More Modern Studies Revisit the Link Between Acne And Diet: mentioning
confidence: 93%
“…Studies that have compared self-report of acne with objective acne assessments have shown that people with acne are not able to accurately report that they have acne. 35 Validity of self-report is moderate at best. Furthermore, recall bias may be playing a role in this study.…”
Section: More Modern Studies Revisit the Link Between Acne And Diet: mentioning
confidence: 99%